Metabolic Symbiosis and immunomodulation: How Tumor Cell-Derived Lactate May Disturb innate and Adaptive immune Responses - Morrot, Alexandre (2018)
Universidade Federal do Rio de Janeiro. Faculdade de Medicina. Rio de Janeiro, RJ, Brasil / Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Imunoparasitologia. Rio de Janeiro, RJ, Brasil.